Pengaruh Keberagaman Produk, Kualitas Produk Dan Citra Merek Terhadap Keputusan Pembelian Kosmetik Wardah Di Batam Center - Maurine Givanka Ningsih; Siagian, Mauli (LPPM Universitas Putera Batam, 2024)
This research aims to investigate the influence of product diversity, product quality and brand image onpurchasing decisions for Wardah cosmetics in Batam Center. The population that is the focus of thisresearch is Wardah consumers at Guardian One mall Batam and the number is based on sales data inAugust 2023 of 317 customers. A sample of 177 respondents was selected using the Slovin formula method.Data analysis was carried out using a multiple linear regression approach. The analysis process includestesting data quality tests, classical assumption tests, influence tests and hypothesis tests. The results ofmultiple linear regression analysis show that product diversity has an influence of 23.1% on purchasingdecisions. Product quality has an influence of 25.8% on purchasing decisions. Brand image has an influenceof 36.0% on purchasing decisions. Findings from testing the coefficient of determination (R2) show thatproduct diversity, product quality and overall brand image can explain around 63.8% of the variation inpurchasing decisions. In addition, the results of the t test and F test indicate that product diversity, productquality and brand image, both partially and simultaneously, have a positive and significant influence on thedecision to purchase Wardah cosmetics at Batam Center.